Endoscopic Cyanoacrylate Glue Injection for Duodenal Varices—A Single-Center Study - Shafiq, Syed; Devarbhavi, Harshad; Patil, Mallikarjun (Journal of Digestive Endoscopy, 2022)
Aim/Objectives Duodenal varices (DVs), although rare, can present with massive, potentially fatal upper gastrointestinal bleeding; however, there are no randomized trials regarding management of this relatively uncommon presentation. We aim to report our experience with endoscopic cyanoacrylate glue injection in patients with DVs.Materials and Methods We retrospectively evaluated the medical records of all patients with portal hypertension at our center between January 2010 and December 2021. Demographic characteristics along with the etiology, location, and effectiveness of cyanoacrylate glue injection for bleeding DVs were collected and analyzed.Results A total of 5,892 patients with portal hypertension underwent endoscopy during the study period, of whom 41 patients (M:F = 29:12) with mean age of 38 years were noted to have DVs. While extrahepatic portal vein obstruction was the commonest etiology (n = 26), the most common site of DVs was the duodenal bulb (n = 21). Twenty-one (51%) out of these 41 patients presented primarily with DV bleeding and underwent endoscopic cyanoacrylate glue injection with successful hemostasis achieved of the index bleed; however, four of these 21 patients had rebleeding between 2 weeks and 12 months of follow-up requiring repeat endotherapy.. While three patients underwent successful repeat glue injections, one patient had recurrent massive bleedings, not amenable to endotherapy and was subjected to duodenal resection with surgical shunt procedure.Conclusion While the prevalence of DVs in portal hypertension patients was 0.7% (41/5892), DVs accounted for 0.42% (21/4889) of portal hypertension-related bleedings. Endotherapy with cyanoacrylate glue appears to be a safe and cost-effective treatment for acute DV bleeding in a resource-limited setting.
Keywords: cyanoacrylate glue; gastrointestinal bleeding; hemostasis; duodenal varices; portal hypertension